2012
DOI: 10.1002/pc.22284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat accelerated aging on tensile strength of three dimensional braided/epoxy resin composites

Abstract: The tensile tests of three‐dimensional (3Dim) and four‐directional (4Dir) carbon fiber braided/epoxy resin composites and carbon fiber woven plain fabric laminated/epoxy composites after heat accelerated aging at 150 and 180°C for 60, 120, and 180 h were carried out respectively. The reason of the changes of tensile property of these composites after different aging period of time at different high temperature was explained. The results of two‐way ANOVA analyzing indicate that the aging time has a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…However, most literatures are confined to thermal oxidation of unidirectional and laminated polymer systems, and there are limited studies on 3D braided composites. Guo et al 25 investigated the effect of thermo-oxidative aging on the tensile strength of 3D and five-direction (5Dir) braided carbon fiber/bismaleimide (carbon fiber/ BMI) composite and noted that the tensile strength decreased after aging for 24 h at 180 C. The observed result of Song and Li 26 was similar to that of Guo et al 25 Song and Li observed that the tensile strength of 3D-4Dir braided carbon fiber/epoxy composite decreased after aging at 150 C and 180 C for 60, 120, and 180 h. It is not difficult to find that past researches are mainly concerned with the effects of thermooxidation on 3D braided composites at the macroscopic scale. However, a systematic study on the thermo-oxidation aging mechanisms of the 3D braided composites has not been performed.…”
Section: Introductionmentioning
confidence: 86%
“…However, most literatures are confined to thermal oxidation of unidirectional and laminated polymer systems, and there are limited studies on 3D braided composites. Guo et al 25 investigated the effect of thermo-oxidative aging on the tensile strength of 3D and five-direction (5Dir) braided carbon fiber/bismaleimide (carbon fiber/ BMI) composite and noted that the tensile strength decreased after aging for 24 h at 180 C. The observed result of Song and Li 26 was similar to that of Guo et al 25 Song and Li observed that the tensile strength of 3D-4Dir braided carbon fiber/epoxy composite decreased after aging at 150 C and 180 C for 60, 120, and 180 h. It is not difficult to find that past researches are mainly concerned with the effects of thermooxidation on 3D braided composites at the macroscopic scale. However, a systematic study on the thermo-oxidation aging mechanisms of the 3D braided composites has not been performed.…”
Section: Introductionmentioning
confidence: 86%
“…To know if there is any statistically significant relationship between the factors (the carbon fiber volume fraction) for response [23] also applied mathematical methods to the analysis of the tensile strength for composite materials, however, the different mathematical model were used. For the results, the two kinds of mathematical models were able to fully explain the relationship between influence factors and tensile strength of composites.…”
Section: One-way Analysis Of Variance Of Tensile Strengthmentioning
confidence: 99%
“…0°is defined that carbon fiber direction oriented along weft direction, and 90°oriented along warp direction. The samples geometry is 250 mm  25 mm  4 mm [23] see Fig. 3 and Table 1, and five samples were tested in every group.…”
Section: Testingmentioning
confidence: 99%
“…Compared to conventional laminated composites, the integrated structure of three-dimensional (3D) and fourdirectional (4Dir) braided composites can improve the TOS of the CFPMCs by enhancing the ability of the fibers to bear the external load and resist delamination, despite the deterioration in the matrix resin and interface properties after thermo-oxidative aging (TOA) for long periods of time [5]. Unfortunately, however, the flexural strength (FS) of the 3D-4Dir braided composite decreases significantly when the fiber/matrix interface performance declines extensively after TOA [6].…”
Section: Introductionmentioning
confidence: 99%